Experimental relationships between surface roughness, irradiation time and photodecomposition rate constant of PVC films doped bypolyphosphates / Emad Yousif ... [et al.]. - Yousif, Emad; Ahmed, Dina S.; Ahmed, Ahmed A.; Hameed, Ayad S.; Yusop, Rahimi M.; Redwan, Amamer; Mohammed, Salam A. (2018)
The photodegradation rate constant and surface morphology of poly(vinyl chloride), upon irradiation with ultraviolet light was investigated in the presence of polyphosphates as photostabilizers. Poly(vinyl chloride) photodegradation rate constant was lower for the films containing polyphosphates compared to the blank film. In addition, the surface morphology of the irradiated poly(vinyl chloride) containing polyphosphates, examined by scanning electron microscopy, indicates that the surface was much smoother compared to the blank film.